Beam position measurement for electron cooler EC-300 and EC-35 - Bekhtenev, E. (Вопросы атомной науки и техники, 2006)
The beam position measurement system of EC-35 and EC-300 is presented in this paper. The electrostatic pickup is used for beam position measuring. The ion and electron currents have alternative part with the magnitude of about 1 mA. The important feature of the beam position measurement system (BPM system) is simultaneous measurements of the positions of both the ion and the electron beams. The resolution of the beam position measurement is about 1 mm, diameter vacuum chamber 300 mm.